Caracterização dos profissionais que atuam em repositórios digitais brasileiros: perfil de competências para bibliotecários - Santos, Elis Gabriela Copa dos (Universidade Federal de São Carlos, 2015)
This work studies open access repositories and the role of information professionals responsible for managing them. The main objective is to understand and delineate the role of the information professional (librarian) in the universe of Brazilian open access repositories as well as conduct a literature review on the changing role of the librarian and their relation to extending the reach of the Open Access movement, and in starting and strengthening the implementation of digital repositories at universities and research centres. The importance of this work is justified by the fact that in Brazil, there are few studies aimed at understanding the relationship between repositories and professionals engaged in their management, as well as the difficulties encountered in this process and the demanded and developed skills by this work. The method adopted was exploratory, using qualitative and quantitative methods, encompassing survey, study, analysis and synthesis of the literature relevant to the study. The empirical data collection phase consisted of the development and submission of surveys to repository managers and others involved in the management of institutional repositories at universities and research centers in Brazil. Furthermore, 20 job announcements for repository staff were analysed, that had been published in England , Ireland, New Zealand and Saudi Arabia between 2012 and the first half of 2014 seeking for information professionals to handle digital information. With the results obtained from the survey responses and the job announcements vacancies, we were able to outline a profile that features five competencies, structured along the dimensions of knowledge, skills and attitudes.
Characterisation of professionals working in Brazilian digital repositories: librarian skills profile
Keywords: Profissional da informação; Competências informacionais; Perfil profissional; Repositórios Institucionais; Acesso Aberto; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO